The REAP Strategy in Action: EFL Students’ Perceptions and Reading Comprehension Enchantment - Rahman, Putri Ramadani Nur; Astrid, Annisa; Sukma, Fitri Alya Okta (The Art of Teaching English as a Foreign Language (TATEFL), 2025)
REAP strategy offers a systematic approach to address challenges face by the students in reading activity. The strategy is divided into managable stages: Reading, Encoding, Annotating, and Pondering. This study aimed to identifying students’ perceptions of the Implementation of REAP strategy on their reading comprehension among 11th-grade EFL grade students in Palembang through a qualitative approach. The interview method chosen was semi-structured to give more insight into the research. The data was collected from students' perceptions of the implementation of the reap strategy which was analyzed using thematic analysis which found that the REAP strategy facilitates understanding of text, REAP encourages content review and retention, REAP promotes comprehension by rephrasing key ideas, REAP increases engagement and attention during reading, REAP facilitates personal connections and critical thinking, lengthy process of REAP and time-consuming implementation of REAP. The REAP strategy effectively improved students’ reading comprehension and critical thinking skills. However, the challenges of its time-consuming and multi-step nature suggest the need for adjustments to its implementation. Educators should consider providing additional guidance during the more complex stages, such as annotation and pondering, and incorporating time management strategies to make the process more efficient and accessible for all learners.